Humanism: A Revolutionary Project I - Baraona Cockerell, Miguel (2021)
This article is the first of a series of three essays on the origins and genesis of the humanist praxis, from its first manifestations thru its main historical moments (blossoms); starting in the 5th century BCE up to the 15th century CE. In this first article of the trilogy, we cover the main philosophers of each of three initial blossoming of humanist praxis in each of them, spanning almost twenty centuries of intellectual and social history. We begin by examining the first ethical-philosophical explicit proposals of a humanist nature in Pericles’ classic Greece, with the works of sophists and Protagoras. In a second point we address the first Islamic Renaissance (VIII-XIII centuries) and its greatest Iberian philosopher Averroes. This second blossoming of humanist praxis is crucial in the general history of humanism because it constituted the necessary bridge between ancient Greece and the third blossoming of the 15th and 16th centuries represented mainly by the greatest humanist philosopher of the European Renaissance, Giovanni Pico de la Mirandola.